On the functional polystability of certain essentially nonlinear nonautonomous differential systems - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For essentially nonlinear differential systems with the limit matrix of coefficients of the first-approximation system, we establish sufficient conditions for functional polystability, which generalizes the notion of exponential polystability.